The Effect of Bay Leaf Decoction on Blood Pressure Reduction in Patients with Hypertension - Budi Rianto; Atira; Emy Salmiyah; Nirmala Aqmarina Shabahati (STIKes Budi Luhur Cimahi, 2026)
Hypertension affects approximately 1.28 billion people worldwide and remains a major contributor to morbidity and mortality, particularly in Indonesia. Conventional pharmacological management often leads to poor adherence, highlighting the need for complementary therapies. This study aimed to examine the effect of bay leaf (Syzygium polyanthum) decoction on reducing blood pressure in patients with hypertension in Cibeunying, Bandung. This quantitative study employed a quasi-experimental design. A total of 30 hypertensive patients were selected using a non-probability purposive sampling technique and divided into an intervention group and a control group. Blood pressure was measured using a digital sphygmomanometer following standard operating procedures. The intervention group received bay leaf decoction for five consecutive days. Before the intervention, 60.0% of participants in the intervention group were classified as having stage 1 hypertension. After the intervention, only 20.0% remained in stage 1 hypertension, while most participants shifted to the pre-hypertension category. Statistical analysis using the Marginal Homogeneity test showed a significant reduction in blood pressure (p = 0.02; α = 0.05). The findings indicate that bay leaf decoction has a significant effect on lowering blood pressure in patients with hypertension. Therefore, bay leaf decoction may be considered as a complementary non-pharmacological therapy for blood pressure management.